Strengthening Strategies for Bugis Language Learning through an AI-Based Local Language Preservation Model in Barru Regency - Sumarlin Rengko HR; Andi Filsah Muslimat; Pammuda; Mutahharah Nemin Kaharuddin; Nasihin; Ridwan Syam; Abdul Rauuf Muri; Zaidul (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The partners of this program are UPTD SD Negeri 32 Barru and the Department of Education and Culture of the Barru Regency Government. This community service activity aims to provide understanding and knowledge to the community regarding policies and the history of local languages as a means to explore the existence of regional languages themselves. The enhancement of understanding about local language policies and history is integrated with a workshop on regional language preservation through the strategic use of Artificial Intelligence (AI) technology to develop and improve practical skills in creating learning processes not only through traditional approaches but also through technological approaches that are effective and easy to use. This program supports the preservation of regional languages through innovative and effective utilization of AI, while also enriching insights into the relationship between technology and regional language learning, thereby producing concrete outputs such as lesson plans, learning modules, or actions that can be implemented after the workshop.